Public Perception of Food Poisoning Reports within the Free Nutritious Meal (MBG) Program - Ludina, Deva Anggreani; Rohid, Nibrosu; Surya, Andi (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2025)
This study aims to analyze public perception regarding media coverage of food poisoning cases within the